If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 12 = 0 Reorder the terms: 12 + 2m = 0 Solving 12 + 2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2m = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 2m = 0 + -12 2m = 0 + -12 Combine like terms: 0 + -12 = -12 2m = -12 Divide each side by '2'. m = -6 Simplifying m = -6
| 8ab/2ab= | | 175.00+2.00x=630 | | (19x+14)+(9x+2)=0 | | 2x^2+11x+21=x^2+14x+49 | | 7x+11=15+3x | | 144x-80=8x+40 | | 9n-12=3n | | 175.00+2.00(50)= | | (9n-12)=(3n) | | 3x^2+25x=28 | | ((6099000-1000000)/6099000)*100 | | -4r+21=-7(5-4r)-8 | | 25+249+100=350 | | 0.48=log(x) | | 10x+20y=230 | | (6x+2)-16=3x | | 25+350+249=100 | | 5-2/x=8 | | 3xsquare+x=14 | | 0.1x=1.5 | | 2x+13=-9x-20 | | 9(x+13)=9x+117 | | 15+7x=8(x-2) | | 5x-3(y)=22 | | -2q+4q=0 | | -1/7x=-8 | | 5(2)-3(-2-2)=22 | | 124/12 | | 10+2x=8(x-2) | | 0.4(x-3)=0.6x+1.8 | | 4(x+2)=4(x+15) | | 7/2x=40 |